Prednosti in slabosti različnih protokolov vodenja vrednosti glukoze v krvi pri kritično bolnih pacientih: pregled literature. - Smajlović, Sedina Kalender (Obzornik Zdravstvene Nege, 2018)
Introduction: Critical care nurses adjust the blood glucose target in critically ill according to the accepted and validated blood glucose control protocols. The purpose of this research was to investigate the benefits and weaknesses of blood glucose control protocols in critically ill patients. Methods: A systematic review of the scientific and professional literature was conducted. The research was done from 1 February 2017 to 8 August 2017. Databases COBIB.SI, The Digital Library of Slovenia -- dLib.si, CINAHL, ProQuest, PubMed and Google Scholar were used for the literature review and analysis. The search was performed with the following key words in the Slovene and English language: benefits, weaknesses, critical care nurses, critically ill, blood glucose and protocols for tight glycemic control. The Boolean AND operator was used. From the total of 1064 results, 15 articles were included in the detailed analysis. The concept analysis model was used to process data. Results: Three thematic areas have been identified: (1) the suitability of different protocols for the management of blood glucose levels, (2) nurses' workload while following these protocols, and (3) the safety of the blood glucose control protocols. The benefits of a computerized blood glucose control protocol lie in better achievement of the target blood glucose concentration. The disadvantages of blood glucose control through control protocols are deviations related to the time allocated to blood glucose measurement. Discussion and conclusion: Some research has established benefits of computerized blood glucose control protocols in terms of technological improvements, reducing the nurses' workload and the safety of blood glucose control protocols. The research makes a contribution to improving the clinical practice in working with critically ill patients.